Animals in Roman Spectacles: A Study of the Interplay Between Spectacle Design and Animal Behaviour - Lapenna, Kathryn Elizabeth (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2024)
This thesis explores the active role that animals played in influencing the design of hunting spectacles (venationes) that were staged in Rome and throughout the Empire from the end of the 1st century BCE to the early 6th century CE. It starts with the premise that animals were not simply cultural objects, but also sentient beings with a specific set of biological characteristics and behavioural repertoires that informed how the Romans used and interacted with animals inside the arena. This confluence of animal behaviour and spectacle design shapes the central questions underlying this study: 1) What behavioural affordances and demands did animals offer, and impose on, the production of venationes? 2) What knowledge did the Romans bring to bear in their responses to animal participants, and how was this informed by human-animal interactions beyond the arena? 3) Are new historical interpretations of venationes made possible by considering the animals' perspective? Specifically: 3a) What does the evidence say about the animals' lived experiences in the arena? 3b) How does this exposure of the animals' lived experiences provide a new perspective and interpretation of the history of venationes that is beyond the human and inclusive of the animals? Over the course of four chapters, I explore the influence of animal behaviour on the design of venationes and the relational manner in which the Romans responded to, and accommodated the natural propensities of, the animals they displayed. Modern animal science knowledge, together with my empirical observations of modern zoo management, are used to help expose and explain the practicalities of spectacle design.
APPROVED
Keywords: Venationes; Animal Behaviour; Zoo Management; Spectacle Design; Roman-Animal Relations; Roman Empire; Roman Entertainment